Students' Attitude to The Application of The Think Talk Write Type of Cooperative Learning Learning Model Relationship with Cognitive Achievement in Islamic Educations - Nurwahdan Nurwahdan; Nadia Husna (STKIP Singkawang, 2022)
This study aims to determine how students' attitudes toward the application of the Think Talk Write Cooperative Learning model are; how Cognitive achievement of students in Islamic Educations subjects; and how is the relationship between students' attitudes towards the application of the Think Talk Write Cooperative Learning model with their cognitive achievement in Islamic Educations subjects in eighth grade at junior high school 1 of Cianjur City. The approach in this study is quantitative, while the method used is the correlation method. Data collection techniques include observation, questionnaires, documentation, interviews and tests. The data analysis technique was carried out with a statistical approach for quantitative data. In analyzing the data that has been collected, the author uses statistical analysis by taking a partial analysis of indicators, normality test, regression test, correlation test and hypothesis testing. The results showed that, 1) The students' attitudes towards applying the cooperative learning model of think talk write type were categorized as positive with a score of 4.34. 2) Cognitive achievement of students in Islamic Educations subjects with a high category score of 83. 3) The relationship between the two variables is (a). The correlation coefficient includes an average score of 0.49 (b). The hypothesis is accepted, t_count is 7.1 and t_table is 0.2542. (c). The degree of influence of the X variable on the Y variable is sufficient, which is 74%. These results indicate that 26% of other factors can affect their cognitive achievement in Islamic Educations subjects apart from students' attitudes towards the application of the Think Talk Write Cooperative Learning learning model